2004
DOI: 10.1017/s0047279404008281
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Points: A Hidden Factor in Reconciling Work and Family Life

Abstract: Despite improvements in childcare provision since the implementation of the National Childcare Strategy in England in 1998, little is known about the practicalities of managing childcare and employment from a parental perspective. It is not recognised that dependent children have to be physically transported from home to the place of care/education, and if transported by the parent the latter usually also has to travel to their workplace in a different location. This article discusses the complexity involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 8 publications
1
43
0
1
Order By: Relevance
“…There were, similarly, accounts of how the complex transport logistics, sometimes associated with childcare arrangements, had to be factored into parents' calculations (cf. Skinner, 2005).…”
Section: Calibration and (In)calculabilitymentioning
confidence: 99%
“…There were, similarly, accounts of how the complex transport logistics, sometimes associated with childcare arrangements, had to be factored into parents' calculations (cf. Skinner, 2005).…”
Section: Calibration and (In)calculabilitymentioning
confidence: 99%
“…also mean that travel to work is not straightforward, especially for parents, especially mothers (e.g. Jarvis, 1999;Kwan, 1999;Skinner, 2005). Rouwendal and Rietveld (1994) found that a lack of geographical mobility resulted in married workers having higher travel-to-work distances in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…The car seems to be a great helper in reaching the necessary flexibility to live a modern and fruitful life, as noted in studies on the role of women (Craig, 2005;Dobbs, 2006Dobbs, , 2007Heine and Mantz, 1999;Skinner, 2003;Schwanen, 2007b) and on time scarcity (Gershuny, 2005;Hjortol, 2005;Skinner, 2005;Southerton, 2003).…”
Section: Understanding Car Mobility Patterns and Choicesmentioning
confidence: 98%